Interaction design: beyond human-computer interaction beyond human-computer interaction - Rogers, Yvonne; Sharp, Helen; Preece, Jenny, 1949- (Chichester, West Sussex, U.K. : Wiley, 2011)
"Rogers, Preece and Sharp are a bestselling author team, acknowledged leaders and educators in their field, with a strong global reputation.They bring depth of scope to the subject, encompassing the latest technologies and devices including facebook and YouTube. Interaction Design offers a cross-disciplinary, practical and process-oriented approach to Human Computer Interaction, showing not just what principals ought to apply to Interaction Design, but crucially how they can be applied. Motivating examples are included to illustrate technical, social, and ethical issues, making the book approachable and adaptable for both Computer Science and non-Computer Science users. Interviews with key HCI luminaries are included and provide an insight into current and future trends. The text comes with a lively and highly interactive companion web site containing a rich set of resources enabling students to collaborate on experiments and designs, take part in competitions, find resources and communicate with others"--
"A revision of the #1 text in the Human Computer Interaction field, Interaction Design, the third edition is an ideal resource for learning the interdisciplinary skills needed for interaction design, human-computer interaction, information design, web design and ubiquitous computing"--
1. Human -computer interaction.
Includes bibliographical references and index.
Keywords: Human-computer interaction; COMPUTERS / User Interfaces